A comprehensive study on piezo-phototronic effect for increasing efficiency of solar cells: A review. (May 2022) - Verma, Ritesh; Chauhan, Ankush; Kalia, Rahul; Jasrotia, Rohit; Sharma, Mamta; Kumar, Rajesh
Graphical abstract: The three-way coupling of piezoelectricity, photoexcitation and semiconducting effect which gives rise to piezo-phototronic. Highlights: The piezo-phototronic effect is the coupling of piezoelectricity with semiconductors and photon excitation. Piezo-phototronic effect modulates the working of solar cells. Piezo-phototronic effect improves the efficiency of different types of solar cells. Abstract: The piezo-phototronic is a combination of three basic principles, ie., piezoelectricity, semiconducting effect and optoelectronic effect, that provides a new working principle for the improvement of current traditional devices. This effect predominantly enhances the performance of solar cells by efficiently modulating the band gap energy. In this review, an effort is made to introduce the piezophototronic effect from its fundamentals to its application in the field of solar cells. The progresses made by the eminent scientists, and researchers in the field of piezo-phototronic modulated solar cells such as semiconductor-based, perovskite-based, multiple quantum well (MQW) based and core/shell based, are also discussed in this paper. It is noted that the piezo-phototronic effect significantly imporved the efficiency of solar cells. Thus, this review is an effort to discuss the recent advancement of solar cells based on piezophototronic effect which can pave a way forward to work extensively on this effect.